Wider Boundaries: The Welfare State and International Remittances - J. Atsu Amegashie; Michael Batu (Center for Economic Studies and ifo Institute (CESifo), 2015)
Recent theoretical work shows that precautionary savings increase in response to an increase in first-order risk. In addition, it is known that the welfare state, being an insurance or consumption-smoothing mechanism, reduces the negative welfare effect of future income uncertainty. We build a model of remittances and savings under income uncertainty and show that an immigrant will increase his remittances in response to a first-order risk decrease in future income. Using changes in the size and generosity of the welfare state as a measure of changes in future income risk, we empirically test the prediction of our model using panel data of bilateral remittances. Our theoretical prediction is supported by the data: there is a positive relationship between a more generous welfare state in host countries and international remittances (i.e., transfers beyond the borders of the welfare state) by immigrants. The boundaries of the welfare state are wider than previously thought.
Keywords: D13; E21; F22; F24; I38; 330; first-order risk; immigrant; precautionary savings; remittances; welfare state